E-084 Recascularization efficacy of the 3d revascularization device versus solitaire in small core ischemic infarcts. (23rd July 2017) - Siddiqui,; Frei, D; Yoo, A; Kirmani, J; Zaidat, O; Lopes, D; Turk, A; Heck, D; Mason, B; Haussen, D; Levy, E; Mehta, S; et al.
Abstract : Introduction: Various thrombectomy devices promise high rates of recanalization and reduction of disability. A recent meta-analysis of the Solitaire device demonstrated its utility as safe and effective in revascularization of large vessel occlusions. The present analysis seeks to determine if good clinical outcome can similarly be achieved by the 3D Revascularization Device for patients with small score infarcts (ASPECTS 8-10). Methods: The 3D trial sought to evaluate the safety and efficacy of the 3D Revascularization Device as compared to the Penumbra System alone in acute stroke intervention. Subjects meeting the per protocol study criteria and presenting with small core infarcts were included in the present analysis. Notwithstanding similarities in baseline characteristics between the 3D ASPECTS 8–10 patients compared to the Campbell cohort (Table I), only patients with small core infarcts were considered for the present analysis. Study outcome on the reduction of disability, defined as mRS 0-2 at 90 days, were compared with the Campbell Solitaire meta-analysis. Results: In total, 105 of 198 patients met the study criteria. While ASPECTS 8-10 data could not be determined for the Campbell cohort, the median NIHSS (3D: 17 [IQR 12–21] vs Campbell: 17 [IQR 13–20] and ASPECTS (3D: 9 [IQR 8–10] vs 9 [IQR 7–10] scores were similar. Reduction of disability (mRS 0-2) data for available trials within the Campbell meta-analysis was extrapolated to evaluated to yield a weighted outcome of 57.7% at 90 days for ASPECTS 8–10 patients treated with the Solitaire device (Table II). Similarly, patients treated with the 3D Revascularization Device demonstrated comparable clinical outcomes, mRS 0–2 in 52.5% (figure 1). Conclusion: Utility of the 3D Revascularization Device with the Penumbra System can achieve favorable long term clinical outcome similar to the use of Solitaire. Disclosures: A. Siddiqui: 2; C; Codman, Medtronic, Guide Point Global Consulting, Penumbra, Stryker, Microvention, W. L. Gore & Associates, Three Rivers Medical, Inc., Corindus, Inc., Amnis Therapeutics, Ltd., CereVasc, LLC. D. Frei: 2; C; Penumbra, Inc., Codman, Microvention, Stryker, Siemens. 4; C; Penumbra, Inc. A. Yoo: 1; C; Neuravi, Inc., Penumbra, Inc.. J. Kirmani: None. O. Zaidat: 2; C; Penumbra, Inc.. D. Lopes: None. A. Turk: 1; C; Penumbra, Inc., Microvention, Stryker, Covidien, Medina Medical. D. Heck: 1; C; Penumbra, Inc.. 2; C; Stryker. B. Mason: None. D. Haussen: None. E. Levy: None. S. Mehta: None. M. Lazzaro: None. M. Chen: None. A. Dörfler: 1; C; Penumbra, Inc.. C. Derdeyn: None. L. Schwamm: None. D. Langer: None. R. Nogueira: None.